Change : how to turn uncertainty into opportunity - Bateman, Curtis; Pleshette, Marche; Cindrich, Andy; Phillips, Christi (Ascent Audio, 2023)
In this guide to navigating the change management process, four FranklinCovey colleagues offer invaluable advice on how to not only accept, but own change, inside and outside of the work office. Listen to inspiring stories from key FranklinCovey team members. Enjoy personal and historical anecdotes, coupled with complementary advice on change management from Bateman, Phillips, Pleshette, and Cindrich. Discover why you should not fear change. As the authors explain in the very first chapter, humans have been fearing and resisting change for a long time. But is there an alternative to this fear and aversion? Yes-you can either get owned by change or decide to own change yourself. Learn how to do just that with tips and advice for every individual, including the manager, the entrepreneur, the employee, or just the average person who fears getting derailed by change. Learn how to implement "The Change Paradox" mentality into your everyday life. In the second half of the book, find a "Change Model" with five Change Paradoxes. Each paradox will not only teach you why avoiding and fearing change is counterintuitive, but will also show you how to implement this newfound advice into your life. Includes exclusive bonus interview of the authors by FranklinCovey CEO Paul Walker